Determination of complete blood count reference intervals by an indirect method for newborns, adults, and geriatric ages - (:unkn) unknown (My University, 2023)
Background: The availability of a reliable reference interval is crucial for clinical decision-making. Correctly de-fined reference intervals for different age groups are currently unavailable for many parameters. Our study aim-ed to determine the complete blood count reference intervals in our region from newborn to geriatric ages with an indirect method. Methods: The study was carried out at Marmara University Pendik E&R Hospital Biochemistry Laboratory be-Tween January 2018 and May 2019 using the laboratory information system data. The complete blood count (CBC) measurements were performed by Unicel DxH 800 Coulter Cellular Analysis System (Beckman Coulter, FL, USA). A total of 14,014,912 test results belonging to infants, children, adolescents, adults, and geriatric ages were collected. We analyzed 22 CBC parameters, and an indirect method was used for reference interval determi-nation. Data were analyzed according to the Clinical and Laboratory Standards Institute (CLSI) C28-A3 guide-line for defining, establishing, and verifying reference intervals in the clinical laboratory. Results: We have established reference intervals from newborn to geriatric ages for 22 hematology parameters [hemoglobin (Hb), hematocrit (Hct), red blood cell (RBC), mean red cell volume (MCV), mean red cell hemoglo-bin (MCH), mean red cell hemoglobin concentration (MCHC), red cell distribution width (RDW), white blood cell (WBC) count, WBC differentials, including percentages and absolute counts, platelet count, platelet distribution width (PDW), mean platelet volume (MPV) and plateletcrit (PCT)]. Conclusions: Our study showed that reference intervals established with data obtained from clinical laboratory databases are comparable to those created using direct methods.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Genel Biyokimya, Genetik ve Moleküler Biyoloji; General Biochemistry, Genetics and Molecular Biology; Box-Cox transformation; complete blood count; indirect method; reference intervals; robust method